Optimizing Social Structures to Improve Adolescents' Physical Health: A Structural Functionalism Approach in China - Congcong Shi; Xiaoling Huang (International Journal of Education and Humanities, 2025)
Since the 1980s, repeated national surveys in China have raised persistent concerns regarding the physical health of adolescents, highlighting a significant decline in their overall fitness. Adolescents' physical health is essential for their well-being and is a critical foundation for the nation’s sustainable development and the effective functioning of its social structure. However, various factors, including changes in lifestyle, educational pressures, and social dynamics, have contributed to the deterioration of adolescents' physical health. Addressing this issue requires a comprehensive understanding of the interrelated social components influencing health outcomes. This study adopts the theoretical framework of structural functionalism to investigate the role of critical social structures—family, school, and society—in shaping adolescents' physical health. The research explores adolescents' complex challenges by analyzing how these functional systems interact and identifying their limitations. The study also evaluates the coordination between these systems and identifies potential pathways to optimize their roles in promoting better health outcomes. Key findings reveal gaps in parental guidance, inadequate school-based physical education programs, and societal neglect of holistic adolescent development. The study emphasizes better alignment and collaboration among families, schools, and societal institutions to address these issues effectively. The research concludes by offering policy recommendations and practical strategies to improve the physical health of adolescents, ultimately aiming to strengthen social stability and drive sustainable development. The insights generated will inform policymakers, educators, and community leaders about fostering a healthier, more resilient younger generation